The never ending debate in cervical spondylotic myelopathy (CSM): Should I approach from the front or back? - Zakaria@Mohamad, Zamzuri (2018)
Cervical spondylotic myelopathy (CSM) is a spinal cord dysfunction caused by the degenerative process of the cervical spine. This process involves biomechanical and biochemical changes affecting the intervertebral disc, facet joints, uncovertebral joints and ligamentum flavum. Upper-motor neuron findings, such as hyperreflexia below the level of compression and gait disturbances are typical presentation of the problem.